PENGARUH SERVICE EXCELLENT, SERVICE QUALITY, DAN SERVICE PERFORMANCE TERHADAP KEPUASAN NASABAH PADA BANK RAKYAT INDONESIA UNIT KECAMATAN KOTA SUMENEP - Haliza, Nur; Setiyarini, Triana (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
BRI Sumenep City District Unit, which is a branch of BRI Sumenep Regency Unit, with various bank products created can provide options for customers to use the financial products and services provided. The objectives of the study are 1) To analyze the influence of excellent service on customer satisfaction at Bank BRI Sumenep City District Unit. 2) Analyze the influence of excellent service on customer satisfaction at Bank BRI Sumenep City District Unit. 3) Analyze the influence of service performance on customer satisfaction at Bank BRI Sumenep City District Unit. The research method was a quantitative approach, with the use of the SPSS For Windows 26 application, the population and sample of 88 respondents with Multiple Linear Regression data analysis techniques. The results of the study show that Service Excellent, Service Qualiyi and Service Performance have a significant influence on Customer Satisfaction, in Bank BRI Sumenep City Unit has a high level of customer satisfaction.